Batteries: Foldable Electrode Architectures Based on Silver‐Nanowire‐Wound or Carbon‐Nanotube‐Webbed Micrometer‐Scale Fibers of Polyethylene Terephthalate Mats for Flexible Lithium‐Ion Batteries (Adv. Mater. 7/2018). Issue 7 (12th February 2018) - Hwang, Chihyun; Song, Woo‐Jin; Han, Jung‐Gu; Bae, Sohyun; Song, Gyujin; Choi, Nam‐Soon; Park, Soojin; Song, Hyun‐Kon
Abstract : Crumply superflexible lithium‐ion batteries based on current‐collector‐free and binder‐free nanowire‐around‐microfiber electrode architectures are presented by Soojin Park, Hyun‐Kon Song, and co‐workers in article number 1705445 . The battery cells, having high loading of active materials, are successfully operated without structural failure and performance loss under folding, crumpling, or even hammering. Their areal energy density is easily controllable by the number of folded stacks of a piece of the electrode mat.